Theory of change: drama and arts-based community engagement for malaria research and elimination in Cambodia - Ean, M; Sanann, N; Callery, J; Pell, C; Peto, T; Tripura, R; Cheah, PY (F1000 Research Ltd, 2021)
Background: Across the Greater Mekong Sub-region, malaria persists in isolated communities along international borders. Arts and drama have been used to reach to communities in Cambodia to engage them in malaria research, prevention and control. The “Village Drama Against Malaria” (VDAM) project was conducted in north eastern and western Cambodia: Stung Treng; Battambang and Pailin provinces during 2016 to 2019. In total, VDAM reached 55 rural villages, 2,378 student participants and 43,502 audience members. Methods: This article presents the results of two stakeholder-led evaluation workshops in which participants collaboratively developed theories of change to better understand the potential and actual impact of arts and drama-based activities on malaria in these communities. The workshops had a particular focus on identifying areas for monitoring and evaluation so that impact can be measured. Workshop participants included village malaria workers, community leaders, professional and student drama performers, and representatives from the local health authorities and the national malaria control programme. Results: Five broad areas were identified as relevant for monitoring and evaluation: logistical and practical challenges; embeddedness and reach of engagement; health knowledge and confidence of young people; effectiveness of communications; impact on malaria. These areas align well with the monitoring and evaluation conducted to date and point to additional opportunities for data collection. Conclusions: The findings from these workshops will inform future engagement strategies, for example, we may engage a smaller number of young people but over a longer period and more in-depth.